INTERNALIZING MULTICULTURAL VALUES IN ISLAMIC RELIGIOUS EDUCATION AT BOARDING SCHOOLS - Akbar, Mahathir; Sahrodi, Jamali; Suherman, Aris; Arifudin, Iis; Zuhri, Saefudin (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: Indonesia’s social, cultural, and religious diversity requires Islamic education to promote tolerance, mutual respect, and social harmony. Purpose: This study aims to examine the internalization of multicultural values in Islamic Religious Education (PAI) at MA Terpadu Tunas Cendekia Babakan Ciwaringin, Cirebon Regency. Method: Using a qualitative descriptive approach, data were collected through interviews, observations, and documentation involving PAI teachers, dormitory supervisors, and students, and analyzed through data reduction, presentation, and conclusion drawing. Result: The findings indicate that multicultural values are internalized through three stages: value transformation, value transaction, and value transinternalization, with key values including tolerance, equality, justice, harmony, and social responsibility. The boarding school system reinforces these values through habituation, role modeling, and integrated socio-religious activities. Conclusion: This study demonstrates that PAI grounded in universal Islamic values can effectively cultivate inclusive and harmonious student character and offers a practical model that may be adapted in other schools, particularly those implementing integrated or boarding-based educational systems.